Child abuse reporting: Role of dentist in India - A review - Bharti Patil; Sushmini Hegde; Anisha Yaji (Wolters Kluwer Medknow Publications, 2017)
Healthy, protected, educated and well developed child population who will grow up to be productive citizens of the country are pillars of the nation. However, they are dependent on their parents or care givers, which makes them vulnerable to abuse. The primary responsibility of protecting children from abuse and neglect lies with the families or the primary caregivers. However, communities and civil society and all other stakeholders are also responsible for the care and protection of children. The injuries of child abuse may be different for different children, however, several types of injuries are characteristic to abuse. Many of these injuries are easily observed by the dental professional in the course of routine dental treatment and are within the scope of dentistry for identification. This literature review shows that there are very few attempts made to report child abuse from dental offices in India whereas it is mandatory to report child abuse in many other parts of the world. This difference could be attributed to laws regarding this matter and lack of awareness and knowledge of the procedures to be followed. The objective of this paper is to review briefly the role of dentist in identifying child abuse and the norms about reporting it in our country.